2020
DOI: 10.1029/2019ja027443
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Mesospheric Neutral Winds and Tides Observed by a Meteor Radar Chain Over China During the 2013 Sudden Stratospheric Warming

Abstract: The neutral winds in the mesospheric and lower thermospheric region obtained from a meteor radar chain within the latitudinal range of 18-53°N were decomposed to examine the latitudinal structures of the tides and mean winds during the sudden stratospheric warming (SSW) event in 2013. The zonal wind reversed from eastward to westward and the westward wind was larger at middle latitudes than that at low latitudes during the SSW. Meanwhile, a sharp increase in the northward wind was noticeable at all stations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…Initially, increased eastward GW forcing acts to drive increased eastward zonal mean zonal winds, ultimately inducing a strong change in the modeled meridional residual circulation ( truev in Figure 6c, see for its derivation Andrews et al, 1987) with enhanced equatorward (and upward, not shown) flow around 100 km, consistent with MR observations (see Li et al, 2020). Through continuity, this residual circulation leads to a net divergence of light species and subsequent high‐latitude decrease in [O], [He], and [H] for the 2012–2013 SSW/MC event, amplifying the expected seasonal decreases (see Figure 3).…”
Section: Resultssupporting
confidence: 80%
“…Initially, increased eastward GW forcing acts to drive increased eastward zonal mean zonal winds, ultimately inducing a strong change in the modeled meridional residual circulation ( truev in Figure 6c, see for its derivation Andrews et al, 1987) with enhanced equatorward (and upward, not shown) flow around 100 km, consistent with MR observations (see Li et al, 2020). Through continuity, this residual circulation leads to a net divergence of light species and subsequent high‐latitude decrease in [O], [He], and [H] for the 2012–2013 SSW/MC event, amplifying the expected seasonal decreases (see Figure 3).…”
Section: Resultssupporting
confidence: 80%
“…Sudden stratospheric warming (SSW) is a large‐scale meteorological event that always occurs with the winter polar stratospheric temperature increasing sharply within several days (Matsuno, 1971; Andrews et al, 1987). This polar event is reported to have a large impact on the atmosphere and on the ionosphere at other latitudes (e.g., Ayarzagüena et al, 2011; Gong Y et al, 2013, 2016, 2018a, b; Coy and Pawson, 2015; Butler et al, 2017; Ma Z et al, 2017, 2018, 2020; Xiong JG et al, 2018; Li N et al, 2020). A major SSW event is associated with a reversal of the zonal mean zonal wind (from eastward to westward) at 10 hPa of 60°N and a positive zonal mean temperature difference between 90°N and 60°N at the 10 hPa level.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies on TW3, the TW3 amplitudes show a distinct increase in the neutral wind during Arctic SSW events (Fuller‐Rowell et al., 2010, 2011; Jin et al., 2012; Wang et al., 2011). And the terdiurnal tides in the observations also show a distinct increase in the neutral atmosphere during some Arctic SSWs (Fuller‐Rowell et al., 2011; Li et al., 2020; Sathishkumar & Sridharan, 2013; Wu & Nozawa, 2015). In this work, the TW3 amplitudes in the neutral wind from SD‐WACCM‐X are shown during the twelve Arctic SSW events in Figures 10 and 11.…”
Section: Discussionmentioning
confidence: 87%